2004
DOI: 10.3386/w10474
|View full text |Cite
|
Sign up to set email alerts
|

R&D Sourcing, Joint Ventures and Innovation: A Multiple Indicators Approach

Abstract: This paper reexamines the limits of the firm in Research and Development (R&D). Using evidence drawn from industrial laboratories we study the causes and effects of R&D sourcing. We begin with the causes of sourcing, finding that Research Joint Ventures (RJVs), the option to purchase and acquire, and research with federal government contribute to sourced R&D. We then consider the effects of sourcing, RJVs, and the firm's internal research on innovation, as defined by patents and new products. Our results are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…A substantial body of literature recognizes the importance of external and complementary knowledge (Antonelli 2000;Bertrand & Zuniga 2006;Cohen & Levinthal 1990;Laursen & Foss 2003;Lissoni 2001;Teece 1986) acquired through strategic partnerships, research joint ventures and M&As (Adams & Marcu 2004;de Faria et al 2010). These studies show that inter-firm knowledge spillovers help in the crossfertilization of new ideas and in the creation of new technology.…”
Section: Literature and Research Questionsmentioning
confidence: 99%
“…A substantial body of literature recognizes the importance of external and complementary knowledge (Antonelli 2000;Bertrand & Zuniga 2006;Cohen & Levinthal 1990;Laursen & Foss 2003;Lissoni 2001;Teece 1986) acquired through strategic partnerships, research joint ventures and M&As (Adams & Marcu 2004;de Faria et al 2010). These studies show that inter-firm knowledge spillovers help in the crossfertilization of new ideas and in the creation of new technology.…”
Section: Literature and Research Questionsmentioning
confidence: 99%
“…Larger studies in the field of financial economics and corporate control are rather undecided, but tend to support the notion of a neutral or negative impact of acquisitions on R&D (Hall, 1990(Hall, , 1999Ravenscraft and Scherer, 1987;Hitt et al, 1991Hitt et al, , 1996Blonigen and Taylor, 2000). In contrast to that, several smaller in depth studies on acquisitions and joint ventures convey a more positive outlook on innovative investment and performance (Gugler and Siebert, 2004;Ahuja and Katila, 2001;Cassiman et al, 2003;Adams and Marcu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on industrial research laboratories in the USA, Adams and Marcu (2004) found that R&D sourcing is mainly driven by research joint ventures with federal government institutions. Sourcing saves R&D costs and secures access to technical services, but it does not affect innovation performance as measured by patents and new products.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%